2014
DOI: 10.1016/j.compag.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Wireless sensor network coverage measurement and planning in mixed crop farming

Abstract: Wireless sensor network technology holds great promise for application in a wide range of areas, both to monitor and control a variety of systems. Whilst the use of sensors has found natural applications within the manufacturing sector, application in agriculture is still in its infancy and has been used largely to only monitor the environment. The use of technology in the agricultural sector to improve crop yield, quality and to foster sustainable agriculture can be regarded as one of the areas that will prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…The ground-reflected signal is available in the first Fresnel zone when h O is greater than or equal to the antenna height. The ground-reflected path has a significant effect on the power of the received signal [58]. For 2.45 GHz, h O is 0.125 m at a distance of 0.5 m between beacons and the subject, 0.958 m at a distance of 30 m, and 1.24 m at a distance of 40 m. Consequently, the height of the beacons nodes must be greater than 1.24 m, and thus the signal from the beacons can arrive intact at the sensor node.…”
Section: Wireless Sensor Network For Elderly Fall Detectionmentioning
confidence: 99%
“…The ground-reflected signal is available in the first Fresnel zone when h O is greater than or equal to the antenna height. The ground-reflected path has a significant effect on the power of the received signal [58]. For 2.45 GHz, h O is 0.125 m at a distance of 0.5 m between beacons and the subject, 0.958 m at a distance of 30 m, and 1.24 m at a distance of 40 m. Consequently, the height of the beacons nodes must be greater than 1.24 m, and thus the signal from the beacons can arrive intact at the sensor node.…”
Section: Wireless Sensor Network For Elderly Fall Detectionmentioning
confidence: 99%
“…Recently, the wireless sensor network (WSN) has been applied to gather the variability of environmental parameters in the agriculture fields, thus precision management can be applied to improve the yield [1]. For the gathering application, several sensor nodes are distributed around a wide geographical area in which the reliability of wireless communication in terms of network coverage is essential [2]. [2] showed that information of radio propagation channel parameters such as path loss helps achieve this requirement.…”
Section: Introductionmentioning
confidence: 99%
“…For the gathering application, several sensor nodes are distributed around a wide geographical area in which the reliability of wireless communication in terms of network coverage is essential [2]. [2] showed that information of radio propagation channel parameters such as path loss helps achieve this requirement.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Azevedo et al [6] researched the propagation characteristics of wireless radio in some complex agricultural environments such as forests with dozens of tree species. Ndzi et al [7] conducted the wireless sensor network coverage measurements in a mixed crop farmland, and proposed a log-linear model. The existing empirical model regard the propagation environment as isotropic homogeneous.…”
Section: Introductionmentioning
confidence: 99%